Some Notes on the Annexed State in Jerbi Berber - Filippov, Nikolay (2019)
Keywords: Linguistique

A Medieval Ibāḍī Tawḥīd in Berber: A Preliminary Survey - Brugnatelli, Vermondo (Local and global Ibadi identities, 2019)
Keywords: Linguistique

Морфология и морфонология языка джерби. во внутригенетической типологической перспективе - Filippov, Nikolay (Institut d'État de Moscou Lomonosov, 2019)
Don de l'auteur
Keywords: Linguistique

Leçons de vie d'un amazigh de Djerba (Tunisie) - Filippov, Nikolay (Berbère Télévision, 2019)
La leçons de vie d'un amazigh de Djerba (Tunisie)
Keywords: Linguistique